Jenis-jenis udang air tawar dan karakteristik habitat di tujuh sungai Kabupaten Aceh Barat Provinsi Aceh - Oktavia, Rita (Biospecies, 2018)
This study aims to determine the species of freshwater shrimp and habitat character in District West Aceh. The research conducted in April - July 2014, include at seven observation site, Used purposive sampling methode. At each station, samples were collected for 30-45 minutes with a length of 3-5 m sampling area along the river in a direction against the current. Samples were taken to the Basic Biology Laboratory of STKIP Bina Bangsa Meulaboh, for further identification. The identification of shrimp based on morphological features, taxonomic characteristics and body measurements. Shrimp habitats in each site are described and documented. There are five species of freshwater shrimp found in West Aceh, ie: Macrobrachium rosenbergii, M.empulipke, M. equidens, M. australe, and M. lanchesteri. There are different species of Freshwater shrimp found in different habitat characters.